INFLUENCE OF INSTRUCTIONAL SUPERVISION IN PROMOTION OF CHILD-FRIENDLY LEARNING ENVIRONMENT IN RURAL PUBLIC PRIMARY SCHOOLS IN MERU COUNTY, KENYA - Kihara, Daniel; Kimiti, Richard; Mulwa, David (European Journal of Education Studies, 2024)
Effective head teachers’ management practices should be aimed at fostering all-inclusive and child-focused learning environments for quality learning and the general well-being of all learners. The purpose of the study was to investigate the influence of instructional supervision in the promotion of a child-friendly learning environment in rural-based public primary schools in Meru County. The study utilised a descriptive survey design and targeted 775 teachers in rural-based public primary schools in Meru County. Simple random sampling was used to select a sample of 155 teachers. Data was collected through questionnaires. Data analysis was carried out through descriptive and inferential statistics. The results of the study revealed a significant relationship between instructional supervision and the promotion of a child-friendly learning environment (r (146) = .22, P = .007). The instructional supervision practices in the study were focused on: supervision of instructional processes, professional development, teacher empowerment, and instruction and guidance on curriculum delivery. Based on the findings, there is a need to improve on direct supervision of instructional processes towards enhancing teaching conditions and quality of learning. The study recommends that head teachers need to receive more in-service training in areas of professional development, and curriculum and assessment. The study further recommends that the government needs to avail more resources for continuous teacher empowerment and professional development plans.
Keywords: child-friendly school, management practices, quality learning and safe learning environment. Instructional supervision, professional development